Efficacy and safety of a T‐type calcium channel blocker in patients with neuropathic pain: A proof‐of‐concept, randomized, double‐blind and controlled trial. (18th April 2018) - Kerckhove, N.; Pereira, B.; Soriot‐Thomas, S.; Alchaar, H.; Deleens, R.; Hieng, V.S.; Serra, E.; Lanteri‐Minet, M.; Arcagni, P.; Picard, P.; Lefebvre‐Kuntz, D.; Maindet, C.; et al.
Abstract: Background: T‐type calcium channels have been shown to play an important role in the initiation and maintenance of neuropathic pain and represent a promising therapeutic target for new analgesic treatments. Ethosuximide (ETX), an anticonvulsant and a T‐type channel blocker has shown analgesic effect in several chronic pain models but has not yet been evaluated in patients with neuropathic pain. Methods: This proof‐of‐concept, multicentre, double‐blind, controlled and randomized trial compared the efficacy and safety of ETX (given as add‐on therapy) to an inactive control (IC) in 114 patients with non‐diabetic peripheral neuropathic pain. After a 7‐day run‐in period, eligible patients aged over 18 years were randomly assigned (1:1) to ETX or IC for 6 weeks. The primary outcome was the difference between groups in the pain intensity (% of change from the baseline to end of treatment) assessed in the intention‐to‐treat population. This study is registered with EudraCT (2013‐004801‐26) and ClinicalTrials.gov (NCT02100046). Results: The study was stopped during the interim analysis due to the high number of adverse events in the active treatment group. ETX failed to reduce total pain and showed a poor tolerance in comparison to IC. In the per‐protocol analysis, ETX significantly reduced pain intensity by 15.6% (95% CI −25.8; −5.4) from baseline compared to IC (−7.8%, 95% CI −14.3; −1.3; p  =   0.033), but this result must be interpreted with caution because of a small subgroup of patients. Conclusion: Ethosuximide did not reduce the severity of neuropathic pain and induces, at the doses used, many adverse events. Significance: This article shows that ETX is not effective to treat neuropathic pain. Nevertheless, per‐protocol analysis suggests a possible analgesic effect of ETX. Thus, our work adds significant knowledge to preclinical and clinical data on the benefits of T‐type calcium channel inhibition for the treatment of neuropathic pain.